Ensuring sustainable development of a region in the strategic period - Prokhorova, Viktoriia; Zalutska, Khrystyna; Fedorova, Yuliia; Obydiennova, Tetiana; Prykhodchenko, Oksana (Eastern-European Journal of Enterprise Technologies, 2023)
The stability of the region’s development, like any system, depends on the effective balance of its subsystems. The effectiveness of subsystems is enhanced by the effective performance of a set of their key components, which depends on the optimization of certain elements by establishing rational relationships between them. Accordingly, the object of the study is the process of rationalization of the constituent elements of territorial community development programs. To solve this issue, a methodical approach to determining the level of development of the region and ensuring its stability in the strategic period is proposed through the rationalization of the effects of mutually determined implementation of business processes of alternative development projects of territorial communities. The expediency of using the coefficient of synchronicity of business processes of certain regional development projects to determine the level of regional development was substantiated. The use of the synchronicity coefficient to ensure the stable development of the respective region is due to the obtained possibility of balancing the specific competitive advantages of territorial communities strengthened by certain effects. These effects are the results of the implementation of optimally formed portfolios of development projects through rational relationships between specific business processes based on the principle of maximum adaptability of their components. The value of the coefficient of synchronicity of the business processes of the portfolio of development projects of Zabolottivsʹka UTC (0.637) made it necessary to take possible measures for their rationalization by implementing individual effects from the interaction of specific business processes. That has made it possible to increase the synchronicity of these business processes to 0.816 and to determine the direction of the possible integration of the studied UTC with other communities with the help of the formed development potential reserves